2011
DOI: 10.1016/j.febslet.2011.08.048
|View full text |Cite
|
Sign up to set email alerts
|

Selective and specific ion binding on proteins at physiologically-relevant concentrations

Abstract: Edited by Miguel De la Rosa Keywords:Insoluble protein Ephrin-B2 Intrinsically unstructured protein Protein-ion interaction Hofmeister series NMR spectroscopy a b s t r a c t Insoluble proteins dissolved in unsalted water appear to have no well-folded tertiary structures. This raises a fundamental question as to whether being unstructured is due to the absence of salt ions. To address this issue, we solubilized the insoluble ephrin-B2 cytoplasmic domain in unsalted water and first confirmed using NMR spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…We thus extended our previous investigations by titrating the 83-residue cytoplasmic domain of ephrin-B2 with 14 salts whose 8 anions are located in the middle, on the left and right sides of the Hofmeister series 96 . Previously the entire domain was found to be insoluble and consequently its structure remains unstudied 97 .…”
Section: 'Yin' Of Protein Aggregationmentioning
confidence: 76%
See 3 more Smart Citations
“…We thus extended our previous investigations by titrating the 83-residue cytoplasmic domain of ephrin-B2 with 14 salts whose 8 anions are located in the middle, on the left and right sides of the Hofmeister series 96 . Previously the entire domain was found to be insoluble and consequently its structure remains unstudied 97 .…”
Section: 'Yin' Of Protein Aggregationmentioning
confidence: 76%
“…To determine the relative contribution of cations and anions to the HSQC peak shifts induced by salts, we monitored the shifts by titrating chloride salts with different cations, including MgCl 2 , KCl, CaCl 2 , and GdmCl. The different chloride salts caused very similar patterns of HSQC peak shifts, suggesting that the observed effects are mostly due to the chloride anion 96 . These results suggest that the HSQC peak shifts observed here are mostly triggered by the asymmetric binding of different anions to the protein residues.…”
Section: 'Yin' Of Protein Aggregationmentioning
confidence: 84%
See 2 more Smart Citations
“…It has been shown that reasonable estimates of z P are obtained from electrophoretic measurements for RNase A (Moody et al 2005) and hen egg white lysozyme (Gokarn et al 2011), both of which exhibit monovalent anion binding. Song's group at the University of Singapore have characterized monovalent anion binding by NMR (Miao et al 2011). Both z eff and NMR measurements reveal that the relative binding strength of anions follows the Hofmeister series (Gokarn et al 2011), suggesting that charge neutralization may be an important contributor to solubility.…”
mentioning
confidence: 99%